BARRIES IN ISLAMIC EDUCATION - Nabila Syafinka Putri; Aisyah Rahma Fitri Tanjung (Proceeding International Seminar of Islamic Studies, 2022)
Indonesia is a country where the majority of the population is Muslim, but ironically many people from children to adults do not understand their own religion. Then many people from social media learn religion but don't want to know, just see and don't want to practice it. To find out how Muslims practice Islamic teachings in life in the family and community, humans must understand well the teachings of Islam with the implementation of Islamic education that is comfortable without any obstacles in the implementation of education so that educational goals are achieved.Keyword: Islamic Education, Obstacles, Solutions